Loyola, l’habitation des jésuites de Rémire en Guyane française - Yannick Le Roux (In Situ)
This communication is an overview of the results of our archaeological work at Loyola, a sugar plantation owned by the Jesuits in French Guiana from 1668 until its ban in 1763. The Loyola plantation in Rémire is located at 10 km from the fortified city of Cayenne and it covers an area just over 1 000 hectares. At one point up to 500 slaves worked at the plantation to produce goods which, when sold to France and other French colonies, brought benefits that were used to support the Jesuit’s missions which aimed to spread evangelization to South American Natives. Loyola illustrates with eloquence the relationship between the Catholic Church and slavery. We present a brief history of this house and the place missionaries occupied in the colonial adventure. We discuss the role they played in the economy of this French colony, considered, rather marginal, in comparison to what is revealed at other the Caribbean examples. Our research has uncovered the master’s house and its outbuildings, a chapel and its cemetery, a blacksmith shop, a pottery, as well as remains of the sugar production such as the mills, boiler and dryer. We also have evidence of coffee production, indigo etc. We have also recovered a large collection of locally made ceramics used for sugar production; imported domestic ceramic and glass and metal farming tools. A project of development of the site is currently engaged, it aims at revealing with the public a illustrating place, in an eloquent way, the memory of slavery in Guyana.